Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s12192-014-0553-0
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of human osteoarthritis symptoms with topical ‘biotherapeutics’: a phase I human trial

Abstract: Osteoarthritis (OA) treatments presently rely on analgesics, which manage pain but fail to restore imbalances between catabolic and anabolic processes that underlie OA pathogenesis. Recently, biologic (biotherapeutic) drugs, which alter the activity of catabolic agents such as nitric oxide and inflammatory cytokines in ways, allowing tissue regeneration, were evaluated for efficacy in OA treatment. These studies failed to demonstrate dramatic abatement of OA symptoms by these drugs, but suggested strategies by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…For this reason, naturally occurring, generally regarded as safe (GRAS) formulations which interact additively or synergistically with β-E to decrease its effective dosage, are of potentially enormous clinical value. Recently, HO-1 inducers have been recognized as being valuable for treatment of cardiovascular, lung, neurological, and kidney disorders (Haines et al 2012 ), along with osteoarthritis as described above (Mahmoud et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, naturally occurring, generally regarded as safe (GRAS) formulations which interact additively or synergistically with β-E to decrease its effective dosage, are of potentially enormous clinical value. Recently, HO-1 inducers have been recognized as being valuable for treatment of cardiovascular, lung, neurological, and kidney disorders (Haines et al 2012 ), along with osteoarthritis as described above (Mahmoud et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous work by the authors of this report suggest that sour cherry seed extract may have potential for the prevention and treatment of I/R-associated pathologies, including diabetes-related ocular disease: previously Bak et al [ 17 ], and later Czompa et al [ 18 ], demonstrated the protective effect of SCSE on ischemic-reperfused rat myocardium; Juhasz et al [ 4 ] confirmed a cardioprotective effect in hypercholesterolemic rabbits; and Szabo et al [ 19 ] proved protection in ischemic-reperfused retina. The extract was further studied toxicologically [ 20 ], which enabled the use of SCSE even in human studies [ 21 , 22 ]. These results are very promising and make SCSE a potential candidate for future drug development and further studies, such as the present one, to analyze the wide spectrum of effects the extract may exert.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the present report have previously demonstrated that activation of endogenous antioxidant defenses with widely available, non‐toxic phytochemicals dramatically inhibits pathological expression of inflammatory cytokines by CD3+ CD4+ T cells in human cells (Mahmoud et al ., ; Mahmoud et al ., ; Csiki et al ., ), and dramatically abates symptoms of osteoarthritis in a human population (Mahmoud et al ., ); moreover, animal studies have recently revealed that tea polyphenols significantly inhibit tissue damage and symptoms of obesity; and obesity‐associated arthritis, by alteration of representation by CD3+ CD4+ T cells activated to express inflammatory cytokines (Byun et al ., ). Therefore, the outcome shown in Fig.…”
Section: Discussionmentioning
confidence: 99%